(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A defense-in-depth (DID) approach for securing critical information infrastructure has been a common method used in cybersecurity. However, holistic design guidelines are lacking which precludes organizations from adopting them. Therefore, this paper sets out to outline and detail a holistic framework using ring-based nested network zone architecture for the design and implementation of highly secured networked environments. The proposed cybersecurity architecture framework offers a structural design for holistically designed N-tier system architectures. Several implementation options, including zoning perimeters, are suggested as being capable of offering different security capability levels by trading off amongst various security aspects. Also, the proposed architecture allows adaptability in implementations for various real-world networks. This paper also proposes an attack-hops verification approach to evaluate the architectural design.